Effects of removing sheep grazing on soil chemistry, plant nutrition and forage digestibility: Lessons for rewilding the British uplands. (10th October 2018) - Marrs, Robert H.; Sánchez, Raúl; Connor, Leslie; Blackbird, Sabena; Rasal, Jennifer; Rose, Rob
Abstract : Rewilding is currently being proposed as a means of enhancing the conservation value of marginal land in many parts of the world. This is especially true in the British uplands where rewilding will almost certainly involve either a reduction in livestock grazing, or its complete removal. The aim of reducing stock numbers would be to reverse the degradation of these ecosystems that has been caused by past over‐grazing. However, little is known about the likely outcomes, or the time‐scales over which such ecosystem recovery might occur. Here, we report preliminary results from a recent study of eight sites at Moor House NNR in the north‐Pennines, where permanent plots with‐ and without‐sheep grazing were established between 1954 and 1967 on a range of typical upland plant communities. Soils and vegetation were sampled, and their chemical properties analysed; for vegetation an assessment of the herbage quality for animal nutrition was also made. No significant differences in soil properties, above‐ground biomass and nutritional status of the vegetation was detected that could be attributed to sheep grazing removal. The only significant effect associated with grazing removal was a reduced digestibility of the vegetation (greater acid detergent fibre concentration) where sheep were removed. These results show that a rewilding strategy that relies only on reducing sheep numbers will have very little impact on ecosystem recovery in terms of soil or herbage chemistry over short‐ to medium‐term time‐scales. Rewilding policies, therefore, attempting to restore ecosystems degraded by over‐grazing must, therefore, be viewed as long‐term (>50 y). Abstract : Herbage biomass was related to elevation: presence/absence of sheep grazing had almost no effect on soil or plant nutrition.